How far can the self be extended? Automatic attention capture is triggered not only by the self-face - Żochowska, Anna; Wójcik, Michał J.; Nowicka, Anna (Frontiers in Psychology, 2023)
The preferential processing of stimuli related to oneself, such as one's own face, is thought to be guided by the high level of familiarity with self-referential information. However, some behavioral studies have shown that people may exhibit a preference for initially unfamiliar stimuli that have been associated with themselves arbitrarily. This raises important questions about the role of early attention in prioritizing newly acquired information linked to the self and whether both highly familiar and newly associated information related to someone personally significant (e.g., a close friend or family member) receive similar attentional benefits. We aimed to tackle both questions by investigating the neural mechanisms involved in processing extremely familiar stimuli, like one's own face or the face of a close-other, as well as stimuli (abstract shapes) that were newly linked to each person. We used a dot-probe paradigm that allowed us to investigate the early stages of attentional prioritization. Our analysis of the N2pc component unveiled that attention was automatically captured by the self-face, a shape associated with oneself, and the face of the close person. However, a shape associated with the close-other did not elicit the same attentional response. Thus, self-prioritization is not exclusively triggered by the familiarity, as information referring to the extended self also benefits from preferential early and automatic attentional processing.